Interferon Production by Macrophages from Adult and Newborn Rabbits Bearing Fibroma Virus-Induced Tumors - Pathak, P. N. (1974)
Tumors were induced in adult and newborn rabbits by inoculation of fibroma virus. After 10 to 14 days, oil-induced peritoneal macrophages were harvested, purified, and tested in vitro for interferon synthesis after stimulation with specific and nonspecific viruses. Peritoneal macrophages from adult rabbits that had initiated tumor regression produced high levels of interferon (titers ranged from 160 to 640) after stimulation with fibroma virus, whereas macrophages from normal adult rabbits failed to produce significant levels of interferon under the same conditions (titers ranged from <10 to 10). Furthermore, fibroma-immune macrophages responded to vaccinia virus and Newcastle disease virus with higher levels of interferon than did normal macrophages. In contrast, macrophages from newborn tumor-bearing rabbits that showed no evidence of tumor regression failed to respond to fibroma virus stimulation with higher levels of interferon (titers ranged from <10 to 10). These macrophages did, however, yield significantly more interferon than newborn control macrophages when stimulated with a good interferon inducer, Newcastle disease virus (titers ranged from 10 to 80). These data suggest that interferon production may be an expression of macrophage activation to fibroma antigens and that macrophage activation is impaired in newborn rabbits with progressive growing tumors.